2023
DOI: 10.3390/genes14091801
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Neuron Degeneration in Huntington’s Disease Using RNA-Seq Based Transcriptome Study

Nela Pragathi Sneha,
S. Akila Parvathy Dharshini,
Y.-h. Taguchi
et al.

Abstract: Huntington’s disease (HD) is a progressive neurodegenerative disorder caused due to a CAG repeat expansion in the huntingtin (HTT) gene. The primary symptoms of HD include motor dysfunction such as chorea, dystonia, and involuntary movements. The primary motor cortex (BA4) is the key brain region responsible for executing motor/movement activities. Investigating patient and control samples from the BA4 region will provide a deeper understanding of the genes responsible for neuron degeneration and help to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 164 publications
0
2
0
Order By: Relevance
“…HD is caused by an increase in CAG trinucleotide duplication of the HTT, which leads to protein aggregation and leads to impaired motor and cognitive function in patients. Therefore, in the treatment of neurodegenerative disease such as HD, the noncoding characteristics of RNA and the interference technology of miRNAs are used to inhibit the expression of mutant HTT and other mutant proteins at the posttranscriptional level to improve the migration defect of immune cells [ 62 64 ].…”
Section: Effect Of Mirnas On Neurodegenerative Diseasesmentioning
confidence: 99%
“…HD is caused by an increase in CAG trinucleotide duplication of the HTT, which leads to protein aggregation and leads to impaired motor and cognitive function in patients. Therefore, in the treatment of neurodegenerative disease such as HD, the noncoding characteristics of RNA and the interference technology of miRNAs are used to inhibit the expression of mutant HTT and other mutant proteins at the posttranscriptional level to improve the migration defect of immune cells [ 62 64 ].…”
Section: Effect Of Mirnas On Neurodegenerative Diseasesmentioning
confidence: 99%
“…With the advances in bioinformatics, these samples have undergone extensive reanalysis through various pipelines ( Seefelder and Kochanek, 2021 ; Sneha et al, 2023 ). Despite the commendable efforts invested in these studies, the differentially expressed genes (DEGs) identified so far have not yielded valuable pharmaceutical or prognostic targets conducive to HD drug development ( Labadorf et al, 2015 ; 2016 ; Lin et al, 2016 ; Agus et al, 2019 ; Seefelder and Kochanek, 2021 ; Sneha et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%